Yusuf Al-Qardhawi's Hermeneutics: An Alternative Moderate Reading of Qur'an - Ahmad Anas (An-Nur International Journal of The Quran & Hadith, 2024)
Contemporary approaches to Qur'anic interpretation have often been criticized for their perceived excesses and controversial methodologies. This research explores al-Qardhawi’s concept of Qur'anic hermeneutics as an alternative method for a balanced and moderate approach to contemporary Qur'anic reading. Al-Qardhawi’s methodology integrates textual, socio-historical, and contextual approaches with modern scientific disciplines, providing interpretive flexibility that remains rooted in maqāṣid al-sharī‘ah while preserving the authority of the Qur'anic text. This study employs a descriptive qualitative methodology, analyzing al-Qardhawi’s hermeneutical concepts through his primary works, supported by secondary sources such as books and journal articles. The findings reveal that the Qur'anic text must be interpreted in alignment with the linguistic norms of its revelation, employing a linguistic approach alongside careful consideration of siyāq (context). Maqāṣid serves as a crucial instrument to validate the meanings of verses and contextualize them for contemporary realities. While the socio-historical approach is significant, al-Qardhawi maintains that the universality of Qur'anic lafāẓ (expressions) transcends the context of revelation and remains applicable to subsequent circumstances. Integration with various scientific disciplines is deemed essential for meaningful interpretation. Additionally, the insights of the Ṣaḥābah (Companions) and early scholars are valuable for comparing and reinforcing interpretative understanding.